Mitophagy and mitochondrial biogenesis in atrial tissue of patients undergoing heart surgery with cardiopulmonary bypass - Allen M. Andres; Kyle C. Tucker; Amandine Thomas; David J.R. Taylor; David Sengstock; Salik M. Jahania; Reza Dabir; Somayeh Pourpirali; Jamelle A. Brown; David G. Westbrook; Scott W. Ballinger; Robert M. Mentzer Jr.; et al. (JCI Insight, 2017)
Mitophagy occurs during ischemia/reperfusion (I/R) and limits oxidative stress and injury. Mitochondrial turnover was assessed in patients undergoing cardiac surgery involving cardiopulmonary bypass (CPB). Paired biopsies of right atrial appendage before initiation and after weaning from CPB were processed for protein analysis, mitochondrial DNA/nuclear DNA ratio (mtDNA:nucDNA ratio), mtDNA damage, mRNA, and polysome profiling. Mitophagy in the post-CPB samples was evidenced by decreased levels of mitophagy adapters NDP52 and optineurin in whole tissue lysate, decreased Opa1 long form, and translocation of Parkin to the mitochondrial fraction. PCR analysis of mtDNA comparing amplification of short vs. long segments of mtDNA revealed increased damage following cardiac surgery. Surprisingly, a marked increase in several mitochondria-specific protein markers and mtDNA:nucDNA ratio was observed, consistent with increased mitochondrial biogenesis. mRNA analysis suggested that mitochondrial biogenesis was traniscription independent and likely driven by increased translation of existing mRNAs. These findings demonstrate in humans that both mitophagy and mitochondrial biogenesis occur during cardiac surgery involving CPB. We suggest that mitophagy is balanced by mitochondrial biogenesis during I/R stress experienced during surgery. Mitigating mtDNA damage and elucidating mechanisms regulating mitochondrial turnover will lead to interventions to improve outcome after I/R in the setting of heart disease.